Review: The Forgotten God: Perspectives in Biblical Theology. Essays in Honor of Paul J. Achtemeier on the Occasion of his Seventy-fifth Birthday - Moberly, Walter (The journal of theological studies, 2004)
The Forgotten God: Perspectives in Biblical Theology. Essays in Honor of Paul J. Achtemeier on the Occasion of his Seventy-fifth Birthday A. Andrew Das Frank J. Matera Pp. xv + 300 Louisville, KY and London Westminster John Knox Press 2002 0 664 22276 5. Paper£20